Designing a Virtual Education Model for Elementary School Teachers in Tehran: An Emergent Grounded Theory Approach - Aryayi, Mona; Shariatmadari, Mehdi; Khorshidi, Abbas; Hamidifar, Fatemeh (International Journal of Education and Cognitive Sciences, 2026)
Purpose: The present study aimed to design a comprehensive virtual education model for elementary school teachers in Tehran using an emergent grounded theory approach.Methods and Materials: This applied qualitative study was conducted using an emergent grounded theory methodology. The research population consisted of experts in educational management who held doctoral degrees and possessed substantial experience through academic publications, research activities, and professional practice in the field. Using purposive theoretical sampling, 15 experts were selected for participation. Data were collected through semi-structured interviews designed to explore the dimensions, components, and indicators of an effective virtual education model for elementary school teachers. Initially, an extensive review of the literature and in-depth interviews with experts were conducted. The collected data were analyzed through open coding to extract initial concepts and indicators. Subsequently, axial coding was employed to categorize these indicators into broader dimensions and components. Finally, selective coding and brainstorming sessions with the experts were used to refine, validate, and finalize the proposed model.Findings: The analysis of qualitative data led to the identification of a multidimensional framework for virtual education in elementary teacher development. Through systematic coding procedures, 92 indicators were extracted and organized into 16 components and 5 overarching dimensions. The findings demonstrated a strong consensus among experts regarding the necessity of integrating technological, pedagogical, organizational, professional, and evaluative dimensions within virtual teacher education programs. The resulting model reflects a comprehensive structure that addresses both the instructional and professional development needs of elementary school teachers in digital learning environments. Expert validation confirmed the coherence, relevance, and applicability of the identified dimensions and components. Following prioritization and refinement, the final model was graphically represented and re-evaluated, receiving confirmation from the expert panel as a valid framework for virtual teacher education.Conclusion: The proposed model provides a comprehensive and context-sensitive framework for enhancing virtual education among elementary school teachers in Tehran. By incorporating multiple dimensions and a wide range of indicators, the model offers educational policymakers, school administrators, and teacher training institutions a practical roadmap for designing, implementing, and evaluating effective virtual professional development programs. The findings highlight the importance of adopting a holistic approach to virtual education that simultaneously addresses technological infrastructure, pedagogical effectiveness, organizational support, professional competencies, and continuous assessment.